Analisis Vegetasi Pada Habitat Gajah Sumatera Di Suaka Margasatwa Padang Sugihan Provinsi Sumatera Selatan - Mahanani, Agnes Indra; Hendrarto, Ign Budi; Soeprobowati, Tri Retnaningsih (Bioma : Berkala Ilmiah Biologi, 2013)
Padang Sugihan Wildlife Reserve covering 86,932 hectares is the natural habitat of elephants in South Sumatra, both wild and managed elephants at Elephant Training Center, Sub Padang Sugihan. This area was used to be production forest. To support life of wild elephants, the vegetation quantity and diversity of vegetation types of feed must be known. This study aimed to analyze the vegetation feed elephants in Padang Sugihan Wildlife Reserve. The method used sampling plots with a size of 1m x 1m and 5m x 5m in five study sites. Data were analyzed using analysis of vegetation to get the importance value index. Species diversity was calculated using the Shannon Wienner Index formula. It was also calculated the value of uniformity of plant based on Simpson formula. The results of importance value index showed that location I was dominated by Echinochloa colonum (L.) Link (76.55%), location II Panicum astagninum R (132.48%), location IIIÂ  Panicum repens L (107.14%), location IV Axonopus caompressus ( 79.48%), location of V Panicum repens L and Cynodon dactylon (L.) Pers. (21.28%), location VI Melaleuca cajuputi (80.77%), and location VII Melaleuca cajuputi (84.08%). The value of the highest species diversity in the location of V at 2.53. The lowest value was in location II at 0.66. The highest uniformity index was 0.92. While the lowest value was 0.37 in the location II. Based on the above results it is necessary to enrich the vegetation species of elephant grass and natural food, especially at locations II and III. Â  Keyword: Padang Sugihan Wildlife Reserve, vegetation analysis, Elephas maximus sumateranus Temminck Â